The Partners in the Property Acted by Removing the Common in the Jordanian Real Estate Property Law - Hisham Jadallah Mansour Shakaterh,; Nawaf Hussein Al-Zu'bi, (Journal of Legal Sciences, 2024)
In the Hashemite Kingdom of Jordan, real estate liquidation proceedings were carried out by the Land Survey Department through a committee called the Real Property Liquidation Committee, Which at that time had the specific jurisdiction of the judges of the new law court, Law No. 13 of 2019" on real estate " grants rights to partners.